Interactive digital storytelling: bringing cultural heritage in a classroom - Rizvic, Selma; Boskovic, Dusanka; Okanovic, Vensada; Sljivo, Sanda; Zukic, Merima (My University, 2019)
Interactive digital storytelling is becoming a popular choice for information presentation in many fields. Its application spans from the media industry and business information visualization, through digital cultural heritage, serious games, education, to contemporary theater and visual arts. The benefits of this form of multimedia presentation in education are generally recognized, and several studies which explore and support the opinion have been conducted. In addition to discussing the benefits, we wanted to address the challenges of introducing interactive digital storytelling and serious games in the classroom. The challenge of the inherent ambiguity of edutainment, due to opposing features of education and entertainment, is augmented with different viewpoints of multidisciplinary team members. We specifically address the opposing views on artistic liberty, at one side, and technical constraints and historical facts, on the other. In this paper, we present the first findings related to these questions and hope to initiate further discussions in this area.